MOLECULAR DETECTION OF OXA-48-LIKE CARBAPENEMASEPRODUCING ESCHERICHIA COLI FROM CLINICAL LABORATORIES IN LAGOS, NIGERIA - Egwuatu , T.O.; Nsa, I.Y; Yousuph, N.B; Asuelimen, F.; Abajigin, E.I; Mujutaba, S.A; Adepoju, F.I; Egwuatu, C.A (UNILAG Journal of Medicine, Science and Technology, 2019)
THE GLOBAL RISING REPORT OF EXTENDED SPECTRUM BETA LACTAMASE (ESBL) AS WELL AS CARBAPENEM RESISTANCE (CR) IS ALARMING. THIS INCREASE IS OF SERIOUS HEALTH CONCERN AS THE CHOICE OF TREATMENT IS LIMITED. WE THEREFORE INVESTIGATED THE INCIDENCE OF ESBL AND CR AMONG URINARY ISOLATES OBTAINED FROM CLINICAL LABORATORIES IN LAGOS STATE. FIFTY-EIGHT URINE SAMPLES WERE COLLECTED AND TESTED. THEIR ANTIBIOTIC SUSCEPTIBILITIES AND ESBL PRODUCTION WERE DETERMINED USING DISK DIFFUSION METHOD. ACCORDING TO THE EUROPEAN COMMITTEE OF ANTIMICROBIAL SUSCEPTIBILITY TESTING (EUCAST), OUT OF THE 58 ISOLATES TESTED, THE MOST INHIBITORY WAS MEROPENEM AND THE kLEAST EFFECTIVE CIPROFLOXACIN. THE RESULTS PANNED OUT AS MEROPENEM (91.4%), ERTAPENEM (74.1%) CEFTAZIDIME (44.8%), CIPROFLOXACIN (15.5%), GENTAMICIN (20.7%), CEFOTAXIME (31%) AND AMOXICILLIN/CLAVUNATE ACID (31%). ESBL PRODUCTION WAS FOUND IN 4 (6.9%) OF THE 58 ISOLATES. ALSO, 6.9% WERE FOUND TO BE CARBAPENEM NON-SUSCEPTIBLE WITH ONLY 5.1% EXPRESSING OXA-48 TYPE CARBAPENEMASE WHILE 1.7% EXPRESSED BOTH OXA-48 TYPE CARBAPENEMASE AND ESBL. AMONG THE CARBAPENEMS, MEROPENEM HAD THE HIGHEST ACTIVITY FOLLOWED BY ERTAPENEM (74.1%). THE DETECTION OF OXA- 48 TYPE CARBAPENEM IN E. COLI POSES THREATS TO THE COMMUNITY HENCE ADEQUATE SCREENING METHODS FOR EARLY DETECTION IS IMPERATIVE TO AID PREVENT AND CONTROL THEIR DISSEMINATION.